2022
DOI: 10.1155/2022/7509620
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Intervention Study of Dictyophora Polysaccharides on Arsenic‐Induced Liver Fibrosis in SD Rats

Abstract: Long-term arsenic (As) exposure can cause liver injury, hepatic cirrhosis, and cancer. Meanwhile, Dictyophora polysaccharides (DIP) have excellent antioxidation, anti-inflammation, and immune protection effects. There are currently few reports on the protection effects of DIP on As-induced hepatotoxicity and its pharmacological value. Therefore, this study was aimed at elucidating the protection of DIP on As-induced hepatotoxicity and exploring its preventive role in antifibrosis. In our study, the SD rat As p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Free radicals subsequently induce lipid peroxidation, which may lead to cellular dysfunction or directly attack cells, triggering their damage ( 51 ). Repeated damage and repair of hepatocytes leads to liver fibrosis ( 52 ). As exposure causes liver injury in rats and liver fibrosis increases with increasing dose and time ( 53 ).…”
Section: Chemical Induction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Free radicals subsequently induce lipid peroxidation, which may lead to cellular dysfunction or directly attack cells, triggering their damage ( 51 ). Repeated damage and repair of hepatocytes leads to liver fibrosis ( 52 ). As exposure causes liver injury in rats and liver fibrosis increases with increasing dose and time ( 53 ).…”
Section: Chemical Induction Methodsmentioning
confidence: 99%
“…Arsenite exposure induced HSC activation and extracellular matrix deposition, and long-term exposure to arsenite induced liver damage, inflammation, and fibrosis in mice or rats (54)(55)(56). Wang et al (52) fed SD rats at a high dose of 100 mg/kg and exposed to sodium arsenite, cell swelling, inflammatory cell infiltration, and fibrous proliferation were evident.…”
Section: Other Liver Toxinsmentioning
confidence: 99%
“…O. lanpingensis polysaccharides (OLP) and Dictyophora polysaccharides could significantly decrease the accumulation of ECM and collagen by upregulating MMPs and collagenase expression, which are essential for collagenolysis [ 64 , 65 ]. Quiescent HSCs play important roles in the progression of liver fibrosis because active HSC can transdifferentiate into myofibroblasts, which produce ECM [ 62 ].…”
Section: Polysaccharides In Different Liver Diseasesmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%